Letter (copy): 'Refugees' - Citrine, Walter, 1887-1983
026-0080-001 Secretary's WMC/FEM/EW/1925. 5th June, 1939. PRIVATE. Mr. J.T. de Lisaso, Basque Delegation, 14, Eccleston Square, London, S.W.1. Dear Mr. de Lisaso, REFUGEES. I have now had an opportunity of seeing your letter of the 3Oth May. I raised this matter at our last General Council meeting, and for your own personal information only I might say that some very useful suggestions were made as to possible temporary work for refugees. The Council are now considering the problem as a whole and are communicating with the affiliated Unions to see whether it is possible for a certain number of refugees to be incorporated in the various industries For a temporary period. I shall be glad if you will keep this confidential, but you can rest assured that the Council are doing everything they can to help these unfortunate people. Yours sincerely, General Secretary. 292/946/26/80